Contraception for women with epilepsy: counseling, choices, and concerns - Reimers, Arne (Open Access J Contracept, 2016)
Approximately 50% of all pregnancies in women with epilepsy (WWE) occur unplanned. This is worrying, given the increased occurrence of obstetrical complications in WWE, including the risk of seizures and their possible consequences for both the mother and the unborn child. Hormonal contraception is usually regarded as highly effective, but it is subject to numerous bidirectional drug interactions with several antiepileptic drugs. These interactions may lead to loss of seizure control or contraceptive failure. Further concerns are loss of bone mineral density and increased seizure activity due to hormonal effects. Many physicians lack sufficient knowledge regarding these issues, and most WWE have never received adequate counseling. Moreover, several studies show that a large proportion of WWE do not take their medicines regularly. This article reviews all of these issues and offers practical recommendations for the management of contraception in WWE.